Narcolepsy associated with Pandemrix influenza vaccine: A systematic review and meta-analysis - Lakoma, Leif (Department of Public Health and Family Medicine, 2022)
This systematic review and meta-analysis forms the mini-dissertation part of the primarily coursework degree of Master of Public Health at the University of Cape Town. The review is divided into three separate parts. The first part constitutes the research protocol which outlines the proposed methods and scope of the review. The second part is a structured literature review further elaborating on the research topic and current knowledge of it. The final third part constitutes the manuscript-ready part of the review. The aim of the review is to systematically explore the current scientific literature regarding the association between narcolepsy and the Pandemrix pandemic influenza vaccine. This particular association has been one of the most studied presumed vaccine adverse effects of the last decade and it has greatly affected the discussion on vaccine safety and vaccine hesitancy still to this date. Despite several studies having been published investigating the association, no systematic review of these studies had been performed prior to the beginning of this this review.